GLUCOSE TOLERANCE STATUS AT 3 TO 18 MONTHS POSTPARTUM OF SRI LANKAN FEMALES WITH A HISTORY OF GESTATIONAL DIABETES MELLITUS - Ajanthan, Saumiyah; de Silva, Asita; Pathmeswaran, Arunasalam; Bhattacharya, Amritendu; Tandon, Nikhil; Patel, Anushka (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Gestational diabetes mellitus (GDM) refers to glucose intolerance, first recognised during pregnancy that usually resolves after birth. Females with previous GDM have an increased risk of developing type 2 diabetes mellitus (T2DM) later in life. Hence, we aimed to investigate the distribution of and risk factors for dysglycaemia in females with previous GDM. METHODOLOGY Females (n=992) from five hospitals in Sri Lanka with GDM as per IADPSG criteria were identified. Of those, 515 (51.92%) followed up at 3 to 18 months postpartum. Sociodemographic, medical and anthropometric data were collected, and 75-g OGTT and HbA1C testing were carried out. RESULTS Within 18 months (median 6 months) of the pregnancy in which they were diagnosed with GDM, 250 (48.54%) females were dysglycaemic, including 50 (9.69%) and 200 (38.76%) with T2DM and prediabetes, respectively as per the ADA criteria. Mean postpartum HbA1C was 5.37 (±0.35)%, 5.70 (±0.45)% and 7.85 (±2.19)% for those with normoglycemia, prediabetes and T2DM, respectively. Females with a higher postpartum BMI [or 1.08 per 1 kg/m2 greater BMI (95% CI 1.03-1.12)], waist circumference [or 1.04 per 1-cm greater waist circumference (95% CI 1.03-1.06)], postpartum screening interval [or 1.13 per 1-month greater screening interval (95% CI 1.03-1.24)], use of insulin during pregnancy [or 5.44, 95% CI (2.35-12.56)] and history of GDM [or 3.64, 95% CI (1.80-7.35)] had a higher likelihood of developing dysglycaemia. CONCLUSION The high post-pregnancy conversion rates of GDM to T2DM reported in this study reinforce the need for mandatory postpartum screening and identification of predictors which could improve accurate risk stratification of patients during pregnancy.